Optimization of Salient Object Segmentation by using the influence of color in Digital Image - Edvin Ramadhan; Iping Supriana Suwardi; Bambang Riyanto Trilaksono (IAES Indonesia Section, 2015)
Human attention is more likely to be interested indifferent objects or striking in image processing called salientobject. Existing approaches worked well in finding the salientobject in this image, but they have not been able to accuratelydetect where objects should stand out due to the influence of lightintensity, there are various object results of salient object detectionin which area is still cut off or do not appear because they do notinclude salient area. We offer solutions to fix these problems byoptimizing salient object detection prioritizing object area aftersalient area, through checking comparison of the color regionlocated around the area of the salient. This Optimization of theapplication is able to improve to 83% from 100 salient object whichhas this problem, and able to produce more natural Saliency Cut.